Effect of symbiotic microorganisms on the foraging behavior of corn - Limas-Martínez, Andrés Gilberto; Amaro-Perea, Emmanuel de Jesús; Herrera-Corredor, Camelia Alejandra; Ballesteros-Rodea, Gilberto; Alvarado-Ramírez, Edwin Rafael; Rivas Jacobo, Marco Antonio (Ecosistemas y Recursos Agropecuarios, 2025)
Promoters of plant growth considered an alternative to increase crop yields and reduce production costs in modern agriculture. The objective was to evaluate plant growth promoters in productivity of various varieties of corn for forage purposes and the behavior of their morphological components, in Soledad of Graciano Sánchez, S. L. P. at 22o 12’ LN and 100o 51’ LO, at 1 835 m altitude. The climate is dry cold, with an average annual temperature of 18o C and annual precipitation of 350 mm. 10 varieties of native or local corn and recrossed hybrids from different origins were used, to which Azospirillum brasilense, Azospirillum b. + Ectomycorrhizas, Azospirillum b. + Bacillus subtilis, Azospirillum b. + Trichoderma harzianum and the control without growth promoter. Plant height, diameter and number of leaves were measured, as well as the yield of leaf, stem, corn and total green matter. A random block statistical model and Tukey mean comparison test at 0.05 were used. The results showed that there was an effect of the varietie on the height, diameter and number of leaves, as well as on the yield of leaves, stem, corn and total, and effects of the plant growth promoters on number of leaves, yield of leaves, corn and total (58150 kg ha-1), and the control showed lower values (47 250 kg ha-1). This shows that the use of growth promoters is an alternative to increase performance.